Advances in three-dimensional graphene-based materials: configurations, preparation and application in secondary metal (Li, Na, K, Mg, Al)-ion batteries. Issue 7 (12th February 2019) - Li, Guangzhe; Huang, Bin; Pan, Zhefei; Su, Xiangyu; Shao, Zongping; An, Liang
Abstract : Recent advances in three-dimensional graphene materials for secondary metal-ion battery applications are reviewed. Abstract : Three-dimensional (3D) graphene materials, consisting of unstacked two-dimensional (2D) graphene sheets serving as building blocks, have been widely reported in recent years. Various synthetic methods have been employed to prepare graphene materials with diverse 3D architectures, which show potential in a wide range of applications such as energy and environmental technologies. In particular, application of 3D graphene-based materials in metal (Li, Na, K, Mg, Al)-ion battery (MIB) systems has been reported often in recent years. However, the critical roles of 3D graphene materials in MIB systems have not been comprehensively discussed. Herein, we first summarize the configurations and preparation of 3D graphene materials. Second, we illustrate the metal-ion storage mechanisms in graphene layers, i.e. intercalation and adsorption. Third, we emphasize the superior functionalities of 3D graphene architectures as supporting and encapsulated materials in MIB applications. Last, we discuss the merits and drawbacks of various 3D graphene architectures in MIB systems. We aim to present a comprehensive understanding of 3D graphene materials and guide directions for future MIB design.